Increased STAT3 Phosphorylation in CD4+ T-Cells of Treated Patients with Chronic Lymphocytic Leukemia and Changes in Circulating Regulatory T-Cell Subsets Relative to Tumor Mass Distribution Value and Disease Duration - Mojca Dreisinger; Zlatko Roškar; Aleš Goropevšek; Andreja Zakelšek; Sara Čurič; Nada Živko; Sebastjan Bevc; Evgenija Homšak (Biomedicines)
Introduction: In mouse models of chronic lymphocytic leukemia (CLL), an effective anti-leukemia immune response was obtained by depleting a specific regulatory T-cell (Treg) subset. While STAT5 signaling could alter the homeostasis of naïve (nTreg) and activated (aTreg) subsets, which are capable of suppressing also CLL patients’ responses to microbial antigens, perturbed STAT3 signaling could drive CXCR5 expression in circulating T-follicular regulatory cells (Tfr) and their entry into the lymph node/tumor microenvironment. Materials and Methods: By using phospho-specific flow cytometry, we monitored STAT signaling/phosphorylation (pSTAT), in vitro responses to Sars-Cov2-antigen-specific stimulation, and circulating Treg subsets in relation to Binet stage and total tumor mass/tumor distribution (TTM/TD) scoring in 62 patients with CLL. Results: The percentage of CXCR5+ Treg significantly increased in patients with Binet stage B disease, and Tfr-like subsets were associated with higher TTM and lower TD. The pSTAT3 levels in CD4+ T-cells were only significantly increased in patients undergoing therapy. Lower nTreg percentages correlated with increased disease duration, and an increased aTreg/nTreg ratio correlated with SARS-CoV-2-antigen-induced STAT5 signaling responses. Conclusions: The results show increased amounts of circulating CXCR5+ Tfr-like subsets in patients with extensive lymph node involvement and augmented STAT3 signaling in patients on therapy. While STAT5 responses may drive nTreg differentiation into aTreg, nTreg decline is associated with increased disease duration.